Analysis of October 23 (Mw 7.2) and November 9 (Mw 5.6), 2011 Van Earthquakes Using Long-Term GNSS Time Series (2017)
The eastern Anatolia provides one of the best examples of an area of rapid deformation and intense contraction that is the consequence of an active continental collision between the Arabian and Eurasian plates leading to large and devastating earthquakes. The latest evidence of the active tectonism in the region is revealed by two remarkable seismic events; Van-Tabanli (Mw 7.2, October 23, 2011) and Van-Edremit (Mw 5.6, November 9, 2011) earthquakes. The study of the earthquake cycle and observation of geodetic and seismic deformation in this region is very important to hazard assessments. In this study, the inter-seismic, co-seismic, and post-seismic movements caused by the above-mentioned earthquakes were investigated using the time series of 2300 days of Global Navigation Satellite Systems (GNSS) observations of the local stations selected from the network of the Continuously Operating Reference Stations, Turkey (CORS-TR). For the inter-seismic period, approximately 1100 daily data were obtained from 21 CORS-TR stations (prior to the earthquakes between October 1, 2008 and October 23, 2011) and evaluated using the GAMIT/GLOBK software. The behaviour of these stations was investigated by processing 1 Hz data from the GNSS stations during the earthquakes on the GAMIT/TRACK software. In addition to October 23 and November 9, the GNSS data on one day before and after the earthquakes was assessed to determine co-seismic deformations. During the October 23 earthquake, hanging-wall deformation of about 60 mm was detected in the SW direction at the MURA station. However, at the VAAN station, deformation of 200 mm (value predicted by time series) was observed in the footwall block in the NW direction. There were not any significant changes at the stations during the November 9 earthquake. For the post-seismic period, the GNSS data from 2012 to 2015 was evaluated. According to the observations, post-seismic deformation continued at the stations close to the epicenter of the earthquake.